Indian Growth References from 0-18-Year-Old children and Adolescents - A Comparison of Two Methods - Khadilkar, Vaman (Indian J Endocrinol Metab, 2019)
BACKGROUND AND AIMS: For updating growth references, large datasets are usually required; collection of these data are expensive and cumbersome. Using a combination of regression equations, Preece Baines model and global LMS values, synthetic growth references for the target population can be generated. The objective of this study is to compare growth references created from continuous anthropometric data using LMS method versus those created synthetically from anthropometric means at key ages. METHODS: De-identified data on 46421 children (26037 boys) from 0-18 years of age from several multicentric studies conducted by the authors' group (2007 to 2017) were included in this study; growth references were constructed using the LMS method. For the production of synthetic references, arithmetic means of heights and weights at key ages were used and global LMS values were used from literature. RESULTS: There was no difference in the medians for height, weight and BMI between the references created by the two methods. The extreme percentile values for height were similar (P < 0.05). However, the spread of values for weight and BMI was narrower in the synthetic references. CONCLUSION: Growth references produced from continuous data differ from those produced synthetically using anthropometric means mainly at the extreme centiles for weight and body mass index; synthetic references take into consideration global trends over several decades.